PENGARUH HARMONIK TERHADAP TEGANGAN KELUARAN PROTOTIP GENERATOR MAGNET PERMANEN KECEPATAN RENDAH - Irasari, Pudji; Fitriana, - (LIPI Press, 2009)
This paper discusses harmonic content in the generator prototype of 1035W, 220V, 3 phase, 333 rpm with the shifting of permanent magnet segment of 15,7 mm. Magnetomotive Force (MMF) caused by stator current is analyzed using Fourier series to obtain harmonics in load condition. Only induction voltage generated by permanent magnet that is taken into consideration of no-load harmonics. Harmonic spectrums are presented in the form of Total Harmonic Distortion (THD) versus. harmonic number. The influence of the highest THD spectrum to the waveform of output phase voltage is analyzed. Theoritical analyses and experimental measurement results of harmonic spectrums and output phase voltage waveform show the similar pattern. The difference of the output phase voltage peak is estimated due to the exceedingly low value of parameter Bm.